Quality of life effects of androgen deprivation therapy in a prostate cancer cohort in New Zealand: can we minimize effects using a stratification based on the aldo-keto reductase family 1, member C3 rs12529 gene polymorphism?. Issue 1 (December 2016) - Karunasinghe, Nishi; Zhu, Yifei; Han, Dug; Lange, Katja; Zhu, Shuotun; Wang, Alice; Ellett, Stephanie; Masters, Jonathan; Goudie, Megan; Keogh, Justin; Benjamin, Benji; Holmes, Michael; et al.
Abstract Background Androgen deprivation therapy (ADT) is an effective palliation treatment in men with advanced prostate cancer (PC). However, ADT has well documented side effects that could alter the patient's health-related quality of life (HRQoL). The current study aims to test whether a genetic stratification could provide better knowledge for optimising ADT options to minimize HRQoL effects. Methods A cohort of 206 PC survivors (75 treated with and 131 without ADT) was recruited with written consent to collect patient characteristics, clinical data and HRQoL data related to PC management. The primary outcomes were the percentage scores under each HRQoL subscale assessed using the European Organisation for Research and Treatment of Cancer Quality of Life questionnaires (QLQ-C30 and PR25) and the Depression Anxiety Stress Scales developed by the University of Melbourne, Australia. Genotyping of these men was carried out for the aldo-keto reductase family 1, member C3 (AKR1C3 ) rs12529 single nucleotide polymorphism (SNP). Analysis of HRQoL scores were carried out against ADT duration and in association with theAKR1C3 rs12529 SNP using the generalised linear model. P-values <0 · 05 were considered significant, and were further tested for restriction with Bonferroni correction. Results Increase in hormone treatment-related effects were recorded with long-term ADT compared to no ADT. TheC andG allele frequencies of theAKR1C3 rs12529 SNP were 53·4 % and 46·6 % respectively. Hormone treatment-related symptoms showed an increase with ADT when associated with theAKR1C3 rs12529G allele. Meanwhile, decreasing trends on cancer-specific symptoms and increased sexual interest were recorded with no ADT when associated with theAKR1C3 rs12529G allele and reverse trends with theC allele. As higher incidence of cancer-specific symptoms relate to cancer retention it is possible that associated with theC allele there could be higher incidence of unresolved cancers under no ADT options. Conclusions If these findings can be reproduced in larger homogeneous cohorts, a genetic stratification based on theAKR1C3 rs12529 SNP, can minimize ADT-related HRQoL effects in PC patients. Our data additionally show that with this stratification it could also be possible to identify men needing ADT for better oncological advantage.